First Report of Pronamide-Resistant Annual Bluegrass (Poa annua). Issue 1 (16th November 2016) - McCullough, Patrick E.; Yu, Jialin; Czarnota, Mark A.
Abstract : A biotype of annual bluegrass with suspected resistance to pronamide was collected from a golf course in Georgia. The objectives of this research were to determine the level of resistance to pronamide and the mechanisms associated with resistance. From POST applications, the pronamide rate that reduced shoot biomass 50% from the nontreated bluegrass measured>10 times higher for the resistant (R) biotype as compared with susceptible (S) biotypes. The R biotype was not controlled by PRE applications of dithiopyr or prodiamine, but was controlled >92% by PRE applications of pronamide at 0.56 and 1.68 kg ha −1 . Mature plants (3- to 5-tiller) of the R biotype absorbed 32% less [ 14 C]pronamide than the S biotype after 72 h in hydroponic culture and accumulated 39% less radioactivity per gram basis of dry shoot mass. The R biotype metabolized [ 14 C]pronamide similar to the S biotype, averaging 16% of the extracted radioactivity. The resistance to POST pronamide applications in the R biotype is associated with reduced absorption and translocation compared with the S biotype.